Restless legs syndrome in frequent blood donors and its relationship with ferritin levels and red cell indices - Davood U. Bava; Gita Negi; Ravi Gupta; Sushant Kumar Meinia; Ranjan Mukharjee; Aswin K. Mohan (Asian Journal of Transfusion Science)
INTRODUCTION: Restless legs syndrome (RLS) is characterized by an urge to move the legs or arms, associated with uncomfortable sensations. Frequent blood donation is one of the known risk factors for RLS. Earlier studies have shown that the prevalence of RLS varies between 4% and 18% among blood donors. The present study was done to assess the prevalence of RLS among repeat blood donors and to find out its correlates in Indian population. MATERIALS AND METHODS: This study was done for a period of 1 year from April 2019 to March 2020. Two hundred donors who fulfilled the definition of “regular donor” by National AIDS Control Organization were enrolled by convenient sampling. Responses to the Hindi version of CHRLS questionnaire for RLS were noted, and history of number of previous blood donations was taken. Estimation of red cell indices and serum ferritin levels was also done. RESULTS: Two hundred donors were selected for analysis. Out of which, 198 donors were males (99%). RLS was reported in only four donors (2%) and all of them were males. This was comparable to population prevalence of RLS reported in this region. CONCLUSION: The prevalence of RLS among repeat blood donors in Indian population was comparable to the general population. Our findings could be reassuring for the frequent donors. Inclusion of basic questions on symptoms of RLS in the donor screening questionnaire can be useful in detecting impending iron deficiency, though its impact on a big scale is doubtful.